Knowledge regarding prevention of varicose vein among nurses - Joshi, Rashmi; Agrawal, Roshani; Shrestha, Archana (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Varicose veins are prominent dilated veins usually present in the lower limbs. High pressures in the veins, leakiness of venous valves, weakness of the vein wall, and inflammation are the key mechanisms that lead to varicose veins. Method: A cross-sectional descriptive study was conducted to find out knowledge regarding prevention of varicose vein among nurses of Patan Hospital, Systematic random sampling technique was used for data collection. The SPSS 16 version was used to analyse. Result: Out of 211 nurses, less than half respondents 73(34.6%) had inadequate level of knowledge, nearly half respondents 101 (47.9%) had moderately adequate level of knowledge and One fifth respondents 37(17.5%) had an adequate level of knowledge regarding the prevention of varicose vein. Conclusion: Majority of the respondents 101(47.9%) had moderate adequate level of knowledge and one fifth respondents had adequate level of knowledge regarding prevention of varicose vein.